PEMAKAIAN DAYA TERHADAP MOTOR PWH137C PENYIRAMAN TANAMAN BAWANG MERAH OTOMATIS BERBASIS (IOT) DI KWT KEMUNING PRABUMULIH - Ari Shandi, Muhammad; Annisah, Masayu; Lutfi, Iskandar (Teknik Elektro Polsri, 2024)
This study aims to evaluate the use of the PWH137C motor in an automatic watering system for shallot plants built in KWT Kemuning, Prabumulih, which is operated via the Internet of Things (IoT). This system is designed to improve the efficiency and effectiveness of watering by using Internet of Things (IoT) technology for remote monitoring and control. To ensure proper water distribution to plants, the PWH137C motor was chosen because of its ability to pump water efficiently and stably. This study focuses on analyzing motor performance, implementing soil moisture meters, and creating system control software. The study shows that the Internet of Things (IoT)-based automatic watering system can improve watering efficiency and ensure optimal growth of shallot plants.